The Emerging Roles of Exosomes in the Chemoresistance of Hepatocellular Carcinoma - Zhang, Jie; Song, Qianqian; Wu, Mengna; Zheng, Wenjie (Current Medicinal Chemistry, 2021)
Hepatocellular carcinoma (HCC) is a common gastrointestinal malignancy with a leading incidence of cancer-related mortality worldwide. Despite the progress of treatment options, there remains low efficacy for patients with intermediate-advanced HCC, due to tumor metastasis, recurrence and chemoresistance. Increasing evidence suggests that exosomes in the tumor microenvironment (TME), along with other extracellular vesicles (EVs) and cytokines, contribute to the drug chemosensitivity of cancer cells. Exosomes, the intercellular communicators in various biological activities, have shown to play important roles in HCC progression. This review summarizes the underlying associations between exosomes and chemoresistance of HCC cells. The exosomes derived from distinct cell types mediate the drug resistance by regulating drug efflux, epithelial-mesenchymal transition (EMT), cancer stem cell (CSC) properties, autophagic phenotypes, as well as the immune response. In summary, TME-related exosomes can be a potential target to reverse chemoresistance and a candidate biomarker of drug efficacy in HCC patients.
Keywords: exosome